Experiences and outcomes of older adults with obesity transitioning from gym- to home-based resistance training due to COVID-19 lockdowns: a mixed-methods analysis of a RCT - Costas Glavas; Jakub Mesinovic; Anoohya Gandham; Mavil May Cervo; Carrie-Anne Ng; Peter R. Ebeling; Elena S. George; Robin M. Daly; Belinda R. Beck; Paul Jansons; David Scott (BMC Geriatrics)
Abstract Background Supervised gym-based high-intensity resistance and impact training (HiRIT) can enhance physical function and muscle strength, but older adults may face challenges affecting adherence to HiRIT, such limited access to facilities and lack of transportation, necessitating a shift towards unsupervised home-based exercise. The aim of this study was to explore experiences and perspectives of older adults with obesity who were required to transition from supervised gym-based HiRIT to unsupervised home-based resistance training (RT) and aerobic training (AT) during COVID-19 lockdowns. Secondary aims were to compare changes in body composition and physical function after 12 weeks between participants required to transition to home-based exercise (“HOME”) and those who were able to continue gym-based exercise (“GYM”). Methods Thirty older adults (60–89 years) with obesity were enrolled from the gym-based HiRIT intervention arm of a 12-week exercise and dietary weight loss trial. Thirteen (43%) participants were transitioned to HOME due to COVID-19 lockdowns. HOME participants were prescribed bodyweight RT and AT exercises, while maintaining the weight loss intervention. Eight HOME participants completed semi-structured interviews post-intervention. Quantitative outcomes including exercise adherence, body composition and physical function were compared to GYM participants. Results Participants’ experiences and perspectives regarding the HOME program encompassed various elements including accessibility, accountability, maintaining physical activity levels, motivation, support from health care professionals, openness to telehealth videoconferencing for support, engagement, lack of equipment, supervision and a structured routine. Both groups had significant reductions in body mass (mean ± SD; GYM: -4.4 ± 0.4 kg, HOME: -6.2 ± 1.2 kg), but HOME demonstrated greater losses in fat mass (mean difference: -3.1 kg, 95% CI: -6.0, -0.3) compared with GYM represented by a large effect size (d = 0.8). Physical function outcomes improved only in GYM (all P < 0.05). Conclusions Older adults with obesity transitioning from supervised gym-based to unsupervised home-based exercise face both supportive and challenging experiences. While accessibility and accountability enhanced their engagement, some participants faced difficulties related to limited equipment and digital support, emphasising areas for improvement in home-based exercise interventions. Home-based exercise may be effective for supporting dietary weight loss, but further research is needed to determine if there are any beneficial effects on physical function. Trial registration Australian New Zealand Clinical Trials Registry (ANZCTR) ACTRN12618001146280; date of registration: 12/07/2018.